Academic contrapower sexual harassment in public universities in Zimbabwe - Mawere, D.; Seroto, J. (South African Journal of Higher Education, 2022)
Sexual harassment in the workplace, including the university, is not a behaviour perceived to be perpetrated only by males. In this article contrapower sexual harassment was investigated to find out whether female students harassed male lecturers at universities, and how harassment manifests with a view to devising measures to mitigate such harassment incidences. A qualitative case study research design was employed to explore the thoughts and experiences of participants at two public universities in Zimbabwe. Purposive sampling was employed in the identification and selection of participants with knowledge and experience of subjecting male lecturers to contrapower sexual harassment. Data were gathered through audio-taped face to face in-depth interviews with female undergraduates using a digital voice recorder. As data were collected through interviews, an iterative process was done. The study verified the existence of contrapower sexual harassment of male lecturers by female students. The study found that the measures that can be taken to mitigate contrapower harassment should include the explicit identification of all behaviours that constitute harassment and their consequences in university codes of conduct and policies. Universities should build a culture of respect in which students and lecturers interact without fear of harassment from either party. Universities need to ensure that lecturers are informed of the available resources should they have disturbing experiences pertaining to harassment from a student.